Corona and financial stability 3.0: Try equity - risk sharing for companies, large and small - Arnoud W. A. Boot; Elena Carletti; Hans-Helmut Kotz; Jan Pieter Krahnen; Loriana Pelizzon; Marti G. Subrahmanyam (Leibniz Institute for Financial Research SAFE, 2020)
This policy letter adds to the current discussion on how to design a program of government assistance for firms hurt by the Coronavirus crisis. While not pretending to provide a cure-all proposal, the advocated scheme could help to bring funding to firms, even small firms, quickly, without increasing their leverage and default risk. The plan combines outright cash transfers to firms with a temporary, elevated corporate profit tax at the firm level as a form of conditional payback. The implied equity-like payment structure has positive risk-sharing features for firms, without impinging on ownership structures. The proposal has to be implemented at the pan-European level to strengthen Euro area resilience.
Keywords: 330; Coronavirus; Financial stability; Risk sharing; Policy measures in the EU